2010
DOI: 10.3176/earth.2010.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of Late Saalian and Middle Weichselian episodes of ice-free lacustrine sedimentation recorded in the Arumetsa section, southwestern Estonia

Abstract: The information obtained from a 21 m thick open-pit section of silty-clayey sediments in the Arumetsa bedrock valley, southwestern Estonia, revealed that lacustrine to glaciolacustrine sedimentation at the site started prior to 151 ka ago and lasted to about the end of marine isotope stage 6 (MIS6) at 130 ka. Further down from the 151 ka age-level to the bottom of the buried valley there are ca 60 m of lacustrine fine-grained sediments, the age of which remains still unclear. The Late Saalian sediments at Arum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Rattas et al . ) reported that during the Middle Weichselian between 44 and 37 ka, ice‐free lacustrine conditions occurred at Arumetsa (SW Estonia). A shallow freshwater basin was mapped and dated to 52–24 ka in western Latvia (Saks et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rattas et al . ) reported that during the Middle Weichselian between 44 and 37 ka, ice‐free lacustrine conditions occurred at Arumetsa (SW Estonia). A shallow freshwater basin was mapped and dated to 52–24 ka in western Latvia (Saks et al .…”
Section: Discussionmentioning
confidence: 99%
“…These dates are in excellent agreement with the age determinations from the basal portion at KKH, which formed during the Saalian deglaciation (MIS 6, Termination II). The regional context within the southern Baltic area is provided by only a limited number of studies that are constrained by absolute age dating of late MIS 6 successions (summarized in Rattas et al 2010). Similarly, there are only a few Eemian surface outcrops across this region, with the majority of the available information on last interglacial conditions derived from borehole data (Andr en et al 2011).…”
Section: Broader Regional Contextmentioning
confidence: 99%
“…These de pos its, there fore, con sti tute suit able ma te rial for chro no log i cal stud ies. The OSL method has been fre quently used in the last de cade to ob tain the age of glacioaquatic, flu vial, lac us trine and ae olian de pos its in the Bal tic re gion (Kalm, 2006;Molodkov et al, 2010;Rattas et al, 2010;Raukas et al, 2010;Zelès et al, 2011;Saks et al, 2012;Satkñnas and GrigienÅ, 2012;Baltrñnas et al, 2013;Kaliñska-Nartiëa et al, 2015a, b, 2016. De spite this, ques tionable OSL ages have been fre quently ob tained from glaciolacustrine and glaciofluvial de pos its (e.g., Raukas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%